Teacher Socialization of EFL Teachers at Public School Levels in Central Mexico (2017)
This study aimed at exploring the processes of teacher socialization and identity formation of nine English as a foreign language teachers at public schools in central Mexico. These teachers began their careers in the National English Program in Basic Education. Qualitative research and narrative inquiry were used as a basis for this research. The data revealed that the teachers’ socialization was somewhat informal in that little was required from them to gain entrance into the program. Once teaching, the participants dealt with challenges in their teaching contexts and the program. From these challenges, the teachers were able to make decisions concerning their future as teachers, forming and imagining their identity.